2018
DOI: 10.1177/0363546518765969
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes and Return to Sports Among Athletes Undergoing Hip Arthroscopy

Abstract: Midterm results of hip arthroscopy in athletes are shown to be safe and favorable. Most athletes return to sports and continue to play after 5 years with the same or higher ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 21 publications
5
47
0
Order By: Relevance
“…13 We believe that labral repair is the gold standard for labral tear treatment, as studies have shown excellent outcomes and high rates of return to sport after labral repair. 19,24,31,33,34,40 However, in cases of irreparable, nonviable, or calcified labra, labral reconstruction has recently emerged as a viable procedure. Literature shows that in these cases, labral reconstruction can restore labral function and is preferred over debridement or excision.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…13 We believe that labral repair is the gold standard for labral tear treatment, as studies have shown excellent outcomes and high rates of return to sport after labral repair. 19,24,31,33,34,40 However, in cases of irreparable, nonviable, or calcified labra, labral reconstruction has recently emerged as a viable procedure. Literature shows that in these cases, labral reconstruction can restore labral function and is preferred over debridement or excision.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…Literature shows favorable VAS, patient satisfaction, and return to sport after labral repair. 4,19,31,33 Furthermore, labral reconstruction is among the most challenging procedures in hip arthroscopy, as evidenced by the handful of surgeons currently performing labral reconstructions. 18,35,36,44,46 This study has several strengths.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…3,6,38 However, only a few studies have used patient-reported outcome measures (PROMs) to present the results, 10,36,37,39 and the reports on the long-or midterm outcome in this patient category are limited. 9,33 Nevertheless, arthroscopic treatment in athletes presenting with FAIS is increasing, and studies suggest that high-level athletes will improve their hip function and have a high rate of return to preinjury activity levels. 2,4,7,8 Follow-up after hip surgery generally includes PROMs.…”
mentioning
confidence: 99%
“…All patients participated in the American Hip Institute Hip Preservation Registry. While the present study represents a unique analysis, data on some patients in this study has been reported in other studies [11,12]. All data collection received Institutional Review Board approval.…”
Section: Patient Selection Criteriamentioning
confidence: 95%